Observation of CP violation in B±→DK± decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; Jäger, Andreas; Kreplin, Katharina; et al. (Physics letters, 2012)
An analysis of B±→DK± and B±→Dπ± decays is presented where the D meson is reconstructed in the two-body final states: K±π∓, K+K− and π+π−. Using 1.0 fb−1 of s=7TeVpp collisions, measurements of several observables are made including the first observation of the suppressed mode B±→[π±K∓]DK±. CP violation in B±→DK± decays is observed with 5.8σ significance.
Im Titel werden "+" und -" untereinander geschrieben: "plus" hochgestellt, "minus" tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Fäber, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, P. Krokovny, C. Langenbruch, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, J. v. Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 24.10.2018